The Influence of Education Level, Work Experience and Work Environment on Employee Performance: Pengaruh Tingkat Pendidikan, Pengalaman Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan - Anggita, Vierlyana; Indayani, Lilik (Indonesian Journal of Law and Economics Review, 2022)
This research is a quantitative research, and the location of this research is PT Karindo Putra Jaya. The population in this study were all employees of PT Karindo Putra Jaya, totaling 283 employees. The sample used is 100 respondents, using a probability sampling technique that is carried out by cluster sampling. Using questionnaires, interviews and unstructured observations to collect data. With the help of SPSS data processing software, multiple linear regression was used for data analysis. The results showed that the level of education had a partial effect on the performance of PT Karindo Putra Jaya employees, work experience had a partial effect on the performance of PT Karindo Putra Jaya employees, the work environment had a partial effect on the performance of employees of PT Karindo Putra Jaya. partially on the performance of employees of PT Karindo Putra Jaya and the level of education, work experience and work environment have a simultaneous effect on the performance of employees of PT Karindo Putra Jaya.